The use of the whole-language approach in instructional materials for English 1 at Colegio de San Juan de Letran - Sta. Teresa, Maria Ruth Quebengco (Animo Repository, 2003)
The researcher made a study on the use of the whole-language approach to help improve freshman students use of the four language skills: speaking, listening, reading and writing. Following the English 1 syllabus of Colegio de San Juan de Letran, modules that gave equal attention to the four language skills using authentic materials like magazines, newspapers and videos were prepared by the researcher. Critical thinking skills were also integrated in the modules. Using authentic materials in the lessons was also found to be an effective way of helping improve the language skills of the students. To find out the effectiveness of the modules, the researcher tested them on selected freshmen students of Colegio de San Juan de Letran during the first semester of school year 2002-2003 (preliminary evaluation) and the summer of school year 2003-2004 (final evaluation). Letran English 1 teachers also evaluated the modules developed by the researcher. Self-made evaluation questionnaires for the English faculty and freshmen students were prepared by the researcher to evaluate the use of critical thinking skills, whole-language approach and authenticity of texts and tasks in the modules. A numerical scale of 1-4 was used to interpret the mean results of the evaluation. Comments and suggestions on the attainment of the objectives were also solicited through the given questionnaires. As a whole, both the faculty and students found the use of critical thinking skills in the modules as Very Satisfactory, while the teachers found the use of the whole-language approach as Very Evident. This shows that the teachers believe that exposing the students to the four language skills in the classroom can help improve students communication skills. Both the faculty and students also rated both texts and tasks as Authentic, which means that activities were close or could be applied to what students may experience in the real world. Furthermore, students and teachers alike found the integration of critical thinking effective and beneficial to language learning.